2001
DOI: 10.1007/s004250100568
|View full text |Cite
|
Sign up to set email alerts
|

Studies on water transport through the sweet cherry fruit surface: II. Conductance of the cuticle in relation to fruit development

Abstract: Water conductance of the cuticular membrane (CM) of sweet cherry (Prunus avium L. cv. Sam) fruit during stages II and III (31-78 days after full bloom, DAFB) was investigated by gravimetrically monitoring water loss through segments of the exocarp. Segments were mounted in stainless-steel diffusion cells, filled with 0.5 ml of deionized water and incubated for 8 h at 25 +/- 2 degrees C over dry silica. Conductance was calculated by dividing the amount of water transpired per unit surface area and time by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 19 publications
3
42
1
1
Order By: Relevance
“…In general, the total conductance of the fruit epidermis is much less than that of leaves (Knoche et al, 2001). Therefore, the water loss from the fruit surface should be lower than that from leaves under the same vapor pressure deficit.…”
Section: Surface Transpiration Of Intact Fruitmentioning
confidence: 99%
“…In general, the total conductance of the fruit epidermis is much less than that of leaves (Knoche et al, 2001). Therefore, the water loss from the fruit surface should be lower than that from leaves under the same vapor pressure deficit.…”
Section: Surface Transpiration Of Intact Fruitmentioning
confidence: 99%
“…Water loss was measured following Knoche et al (2001). Briefly, petals were sealed across the opening of cylindrical water-filled chambers with silicon grease applied along the ring of petal-chamber contact.…”
Section: Water Permeability Analysesmentioning
confidence: 99%
“…This humidity-sensitive polar path of cuticular water permeability is arranged in parallel with the humidityindependent non-polar path formed by lipophilic wax components of the cuticle. Cuticular conductance can be affected by cuticle thickness (Knoche et al, 2001), which varies according to fruit growing conditions. It has been shown that cuticle thickness of some plants was reduced when growth occurred in high-humidity environments (Tribe et al, 1968).…”
Section: Postharvest Behaviour In Rela-tion To Preharvest Factorsmentioning
confidence: 99%